The Institutionalization Process of Turkish Press Through The Changes in Bylaws of Press Associations - ÖZCAN, ÖMER FARUK (MARMARA UNIV, FAC COMMUNICATION, 2016)
As a crucial component of social life, Turkish press has played a significant role in Turkey's political transformation. Therefore analyzing the transformation of the Turkish press provides us insight with respect to the political transition processes from the end of the Ottoman Empire to the beginning of the Republic of Turkey. This paper aims at understanding the mentality change in the press through the analyses of the structural changes in press associations established in between 1908-1946. Following a historical approach, the statutes of press associations are investigated and analyzed in terms of aims, press ethics, self-governance and copyrights.
Keywords: Turkish Press; Press History; Press Association; Organizational Structure